A Class of Nonlocal Fractional Evolution Equations and Optimal Controls - Agarwal, Ravi P.; Asma; Lupulescu, Vasile; O’Regan, Donal (Journal of Applied Nonlinear Dynamics, 2026)
In this paper we study the existence of solutions for a class of semilinear fractional differential equations with nonlocal conditions and involving abstract Volterra operators. The existence of an optimal solution for a class of fractional control problem involving Caputo fractional derivatives is obtained. An example is presented to illustrate our main result.